2022
DOI: 10.1177/07334648221079110
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality Reports From Family Caregivers and Matched Non-caregiving Controls in a Population-Based Study

Abstract: The stress of family caregiving may affect many health-related variables, including sleep. We evaluated differences in self-reported sleep quality between incident caregivers and matched non-caregiving controls from a national population-based study. Caregivers and controls were identified in the Reasons for Geographic and Racial Differences in Stroke (REGARDS) study and matched on seven different demographic and health history factors. Caregivers reported significantly longer sleep onset latency than controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…Caregivers of PLwD tend to spend less than 7 hours in bed, having high amounts of wake, impacting not only sleep quantity but also sleep quality 6 . Studies have found negative impacts in sleep latency 1 , 7 , 18 , 27 , 32 , sleep fragmentation 13 , 18 , 19 , 26 , shorter sleep duration 3 , 18 , and low subjective sleep quality 1 , 2 , 33 . In smaller proportions, they found insomnia 8 , use of medication 1 , 29 , daytime dysfunction 3 , and low sleep efficiency 1 , 6 ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Caregivers of PLwD tend to spend less than 7 hours in bed, having high amounts of wake, impacting not only sleep quantity but also sleep quality 6 . Studies have found negative impacts in sleep latency 1 , 7 , 18 , 27 , 32 , sleep fragmentation 13 , 18 , 19 , 26 , shorter sleep duration 3 , 18 , and low subjective sleep quality 1 , 2 , 33 . In smaller proportions, they found insomnia 8 , use of medication 1 , 29 , daytime dysfunction 3 , and low sleep efficiency 1 , 6 ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…This systematic review aimed to analyze the relationship between burden and sleep disturbances in caregivers of PLwD. Recent studies have found that the most impaired sleep components were sleep latency (the time the person takes to fall asleep after going to bed) 1 , 5 , 18 , 26 , 33 and sleep fragmentation (sleep interruptions through the night) 13 , 18 , 19 , 26 . In addition, our findings corroborate the hypothesis that caregivers tend to spend less than seven hours in bed, leading to negative impacts on sleep quality and quantity, suggesting that this population has shorter sleep duration 3 , 18 , low subjective sleep quality 1 , 20 , maintenance insomnia 8 and low sleep efficiency 1 , 6 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eligible caregivers who consented to participate in the CTS then participated in a structured telephone interview that collected additional information regarding their mental health, well-being, and caregiving experiences (Roth et al, 2020). More thorough descriptions of the CTS and the REGARDS study are provided elsewhere (Haley et al, 2020;Blinka et al, 2022), including a timeline of data collection sessions (Roth et al, 2020). The RE-GARDS and CTS were reviewed and approved by the Institutional Review Boards of the University of Alabama at Birmingham and Johns Hopkins University, respectively.…”
Section: Datamentioning
confidence: 99%